Detailed Literature Review: Antecedents Affecting the Flight Risk or Turnover Intention of Professionals - Singh, Archana (Ushus Journal of Business Management, 2021)
Employee turnover has attracted significant research worldwide because of the high cost it entails. These costs include recruitment, selection, training, adjustment time, possible product, and/or service quality problems which often exceed hundred percent of the annual salary for the position being filled. Understanding the factors that influence the turnover gives organisations the opportunity to reduce selection and training costs, increase employee morale and customer satisfaction and enhance organisational productivity. This paper traces the work done by researchers in understanding the flight risk or Turnover Intention behaviour of professionals and thus helps understand and curtail turnover thereby curtail costs for organisations.